ANALISIS YURIDIS POLITIS KEBIJAKAN MAKAN BERGIZI GRATIS (MBG) ANTARA MANDAT KONSTITUSI WELFARE STATE DAN TANTANGAN ANGGARAN PENDIDIKAN - Ahmad Nurafendi; Mustofa Kamil; Eduardo Retno; Firmansyah Mahmud; Ronny Erlando (Berajah Journal, 2026)
The Free Nutritious Meal (MBG) program is a national strategic policy launched by the new administration as an effort to accelerate the quality of Human Resources (HR) towards the Indonesia Golden 2045 vision. As a massive nutritional intervention instrument, this policy aims to break the chain of stunting and enhance the cognitive capacity of students across Indonesia. Despite its strong welfare orientation, this policy has sparked legal and constitutionality polemics, particularly regarding its funding sources. A crucial debate arises when the MBG budget allocation intersects with the mandate of Article 31 Paragraph (4) of the 1945 Constitution, which requires the state to prioritize the education budget at a minimum of 20% of the State Budget (APBN). The use of the education function budget for nutritional fulfillment raises questions regarding the risk of distorting the core objectives of national education. This research employs a qualitative descriptive method with a normative legal approach. Data were collected through literature studies of various primary legal materials, such as the 1945 Constitution, the State Budget Law, and implementing regulations related to the National Nutrition Agency, as well as secondary legal materials including theories of the welfare state and public policy. The study finds that substantively, the MBG policy constitutes a fulfillment of human rights to health and welfare in accordance with Article 28H and Article 34 of the 1945 Constitution. However, procedurally and constitutionally, this policy risks being unconstitutional if not accompanied by a strict separation of budget structures to prevent the erosion of basic educational implementation needs. Without a legal framework at the Statutory (Law) level to ensure accountability and sustainability, this policy is vulnerable to being perceived as a pragmatic political tool that threatens the long-term fiscal stability of the education sector.